Risk assessment using pool fire and health index analysis at bioenergy plant - Mohd. Fuad Ngo, Juliza (2008)
Risk assessment is recognized as a complete process of identifying a hazard and evaluating the risk either in absolute or relative terms. Risks at Vance Bioenergy Sdn Bhd are measured by identifying the most hazardous and flammability of raw material used in methyl ester and refined glycerin plant. As a result, methanol is the most flammability; hence the study focuses at the methanol storage tank. The area affected is determining using pool fire analysis. Besides that, the study also identifies the air emission from the stack sampling based on the secondary data obtained from preliminary environmental impact assessment study. The health effects from the air quality within Vance Bioenergy Sdn Bhd. and their surrounding areas are determined constantly to verify whether it could affect to human or not. Overall, the health index at three sampling point showed averagely 0.7, which is less than 1 and presume it could not give any significant impact to health. Beside that, the air quality also complied with the Malaysian Recommended Environmental Air Quality Guidelines. An Emergency Response Plans (ERP) is proposed to mitigate and prevent any risk or accident during the plant operations.